THE IMPACT OF NUSANTARA CAPITAL CITY RELOCATION TO THE ECONOMIC PERFORMANCE IN INDONESIA BASED ON COMPUTABLE GENERAL EQUILIBRIUM INDOTERM ANALYSIS - K.P.Suharyono Soemarwoto Hadiningrat (JIPOWER : Journal of Intellectual Power, 2024)
The relocation of the capital city to Nusantara is part of a public policy initiative undertaken by the Joko Widodo administration. The aim is to transform the governance center from Java-centric to Indo-centric in the East Kalimantan region, thereby achieving balanced development between the western and eastern regions of Indonesia. This research aims to provide empirical evidence on the positive and negative impacts of the capital relocation on Indonesia's overall economic performance and the economic performance of East Kalimantan specifically. The analysis employs a quantitative approach using the Computable General Equilibrium (CGE) model IndoTERM (The Enormous Regional Model). The research findings indicate that the relocation of Indonesia's capital city from Jakarta to East Kalimantan will have a positive impact on the economic performance of East Kalimantan province. Specifically, it is projected to increase the nominal Gross Domestic Regional Product (PDRB) growth rate by 0.190 or 19% from the baseline and the real PDRB growth rate at current prices by 0.100 or 10% from the baseline. This is expected to positively influence the overall economic growth rate and generate improved economic performance, particularly in East Kalimantan and Indonesia as a whole. Based on the research findings, the following recommendations are made for the Government of the Republic of Indonesia: a) prepare a more comprehensive Nusantara Capital Relocation Plan that involves all stakeholders, making it a "national consensus and endeavor."; b) conduct a comprehensive and in-depth assessment of the relocation from various aspects, including ideology, politics, economics, social, cultural, defense, and security; c) Develop programs for the development of surrounding communities and newcomers to ensure they possess adequate quality and capabilities, enabling them to become productive and competitive Human Resources (HR) rather than becoming mere bystanders or marginalized.